Assessing the cognitive complexity of cyber range environments. (January 2020) - Roque, Antonio; Stetson, Douglas; Hannon, Daniel J
We present a conceptual foundation and empirical framework for modeling cognitive complexity in cyber range event operating environments. Definitions of key concepts, such as cognitive complexity, task difficulty, and Blue Team cognitive workload, are informed by the literature of human factor engineering. This is followed by an approach to assessing cognitive complexity as experienced by a Blue Team in a given cyber range event operating environment, and a validation of that assessment method.